Unraveling the Effectiveness of Blended Learning: Key Factors for Effective Implementation from the Perspective of Senior High School Students - Samson, Julia Carelle M.; Abrenica , Keona Faye C.; Delfin , Riane Jesserine M.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2023)
Blended learning integrates in-person and online learning, resulting in a flexible learning environment. The main objective of this study is to determine the perceived level of blended learning effectiveness among Grade 12 STEM students from a Philippine private university based in the City of Manila. It also examined the relations between the learners' attitudes, level of efficacy in using the LMS, and academic support received from parents and teachers. A total of 202 SHS students answered the survey questionnaire. Descriptive statistics, Spearman Rho, and multiple regression were employed to analyze the data. Findings show a positive attitude of the learners on the use of blended learning as a mode of learning (x͂ = 4), high self-efficacy on the use of LMS (x͂ = 4), high academic parental support (x͂ =4) and high teachers' support (x͂ = 4). The findings of their perceived effectiveness of blended learning show a high rating with a x͂ = 4. The Spearman Rho tests found each variable's correlation with blended learning effectiveness. Both instructors' academic support for students and learners' attitudes had a strong positive correlation; LMS self-efficacy had a moderately positive correlation, while parents' academic support had a weak positive correlation. Multiple regression tests revealed that learners' attitudes, academic support from parents and teachers, and students' level of efficacy in using the LMS design feature all predict effective blended learning.